2020
DOI: 10.1080/1828051x.2020.1763861
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of monoclonal antibodies against deoxynivalenol

Abstract: To prepare broad-spectrum and specific monoclonal antibodies (mAb) against deoxynivalenol (DON), DON-BSA was synthesised by the carbonyl diimidazole method as an artificial antigen to immunise Balb/C mice, and the coated DON-OVA was synthesised by the carbodiimide method to detect anti-DON antibodies. Monoclonal antibodies were screened by indirect ELISA and indirect competitive ELISA. A hybridoma cell line (4F3) capable of stably secreting DON antibody was obtained. The titre of antibody in the culture supern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…e ZEN pAb titers were tested through indirect noncompetitive ELISA (inELISA) using the procedure described by Han et al [34]. e coating antigen ZEN-OVA was diluted in CBS at 2 μg/mL, and 100 mL/well was added to the 96-well microplate and incubated at 37.8°C for 2 h. After washing with PBST three times, unbound active sites were blocked with 250 μL/well of blocking buffer at 37.8°C for 1 h or 4°C overnight.…”
Section: Identification Of Zen Pab 281 Titers Measurementmentioning
confidence: 99%
“…e ZEN pAb titers were tested through indirect noncompetitive ELISA (inELISA) using the procedure described by Han et al [34]. e coating antigen ZEN-OVA was diluted in CBS at 2 μg/mL, and 100 mL/well was added to the 96-well microplate and incubated at 37.8°C for 2 h. After washing with PBST three times, unbound active sites were blocked with 250 μL/well of blocking buffer at 37.8°C for 1 h or 4°C overnight.…”
Section: Identification Of Zen Pab 281 Titers Measurementmentioning
confidence: 99%
“…The results showed that the CDI method described by Maragos et al [ 28 ] and the improved method had the best effects, and the 3-hydroxy group on the DON molecule had a greater chance of reacting. Therefore, in this study, the hydroxyl group at the C3 position of the DON molecule was successfully covalently coupled to the amino group of the carrier protein BSA by the CDI activation method to obtain the artificial antigen DON-BSA without blocking the hydroxyl group at any site, and the imidazole group was directly introduced to achieve coupling with the carrier protein BSA [ 29 ]. The artificial antigen synthesised by this method was not very different from that produced by the preparation method reported by Lee et al [ 30 ] in the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…DICH was coupled with KLH as the immunogen (DICH-KLH) using the carbodiimide method. 20–22 Briefly, 10.0 mg of DICH and 12.0 mg of N -hydroxysuccinimide were dissolved in 400 μL of DMF. Then, 24.0 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride dissolved in 50 μL of MES (0.1 mol L −1 , pH 4.0) was added with continuous stirring for 8 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%